LE DEBOLEZZA STRUTTURALE DEL LINGUAGGIO NELLA SETTIMA LETTERA DI PLATONE - Forcignano, Filippo (Revista Ética e Filosofia Política, 2018)
The aim of the paper is twofold. Firstly, I am to provide an overview of Plato’s Seventh letter epistemological passage usually called “philosophical excursus”. Secondly, I also analyse the main reason of human inability to perfectly know the highest things which Plato identifies in the text: the “weakness of logoi”. The argument is that it is impossible for human beings to go beyond name, discourse, image, and science (i.e. a set constituted by right opinion, science in strict sense and intellection). Therefore, we cannot grasp the “essence” of the thing itself without its “qualities”. In the last part of the paper, I reject both the “mystic” interpretation (according to which we have a non-logical access to the truth) and the “noetic” interpretation (according to which we have a rational but non-propositional access to the truth).